Peningkatan Motivasi dan Prestasi Belajar Menulis Teks Narasi dengan Teknik Student Teams-Achievement Devisions (STAD) Peserta Didik Kelas XA SMA Negeri 5 Kota Magelang - Eva Ratihwulan (TRANSFORMATIKA, 2018)
This research is aimed to improve students' motivation and learning outcomes. The action used in improving the two things is the learning process with STAD technique. This study uses three stages: Pre Cycle, Cycle I, and Cycle II, each cycle using two meetings. Research data were obtained from a student questionnaire and test with multiple choice questions. Questionnaire to know the development of learning motivation, while the test with multiple choice questions to know the development of learning outcomes. The research data is analyzed descriptively-qualitative. The results of the study explain that the implementation of learning with STAD techniques can improve student's motivation and achievement. Learning motivation in Pre Cycle obtained an average of 23.47 (medium category). While in Cycle I the average learning motivation increased to 26.57 (medium category). Percentage of students achieved high category score of 4 students (13%). Furthermore, in cycle II the average learning motivation of 33.87 (high category). Percentage of students obtained a great and very high category score of 22 students (73.3%). Thus until the end of Cycle II, learning motivation has increased. While the results of learning on the Precycle obtained an average of 61.93 (enough category), in the first cycle increased to 69.53 (enough class), in Cycle II obtained an average of 78.77 (right type). Furthermore, it is known that the percentage of learning mastery in the Pre Cycle of 3%, Cycle I of 31%, then in cycle II the rate of learning mastery increased to 86.66%. Thus until the end of Cycle II, student learning outcomes have increased. Based on the above data can be concluded that the implementation of learning STAD technique can improve learning motivation and student learning outcomes.